Pengenalan Waktu Tradisional "Bulan Berladang "Kesamaannya dengan Keadaan Meteorologis dan Pemanfaatannya untuk Pertanian - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
"Bulan Berladang" (BB) is the name of the Daya's traditional time reckoning in West Kalimantan Indonesia. BB has been used by the farmers as a guidance for agricultural activity since a long time ago. Three types of BB, but principally all types use the same indicators. The indicators are a position of Bintang Tiga (BT) (not yet known its astronomy name) and the crocodile habit. The position of BT and the crocodile habit are used as indicators of the best time to commence land preparation and rice sowing for their shifting cultivation system. By using BB the farmers claim of success. When BB calendar is overlaid on the mean monthly rainfall-potential evapotranspiration balance, it is known that the best time for land preparation and rice sowing coincide with the period of rainfall deficit or coincide with a relatively small rainfall surplus.